Synthesis and Structural Characterization of Manganese(II), Iron(III), Cobalt(II) and Copper(II) Complexes of 3-[1-(3,4-Dihydro-6-methyl-2,4-dioxo-2H-pyran-3- yl)ethylideneamino]-benzoic Acid - Mane, V.G. (Asian Journal of Chemistry, 2010)
The solid complexes of Mn(II), Fe(III), Co(II) and Cu(II) with Schiff base derived from 3-acetyl-6-methyl-(2H)-pyran-2,4(3H)dione (dehydroacetic acid) and m-aminobenzoic acid have been synthesized and characterized by elemental analysis, conductometry, thermal analysis, magnetic, IR, UV-vis and NMR spectral studies. From the analytical and thermal data, the stoichiometry of the complexes has been found to be 1:2 (metal:ligand). The low conductance values suggest that the complexes are non-electrolyte. IR spectral data suggest that the ligand behaves as a dibasic bidentate ligand with N:O donor sequence towards metal ions. The physicochemical data suggests that all the complexes possess octahedral geometry. They are also screened for antimicrobial activity.